People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This Selected Issues paper examines the fiscal outlook and policy options for the Hong Kong Special Administrative Region. The paper provides indicative estimates of how revenue and expenditure might evolve in the next five years under two fiscal consolidation scenarios with a different mix of revenue/expenditure measures to bring the fiscal position to balance by FY2006. The paper examines different revenue raising measures in light of the findings by the Advisory Committee on new Broad-Based Taxes. It also offers some thoughts on areas where potential expenditure savings could be made.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet